Radiografi Oss Pedis dengan Sangkaan Dislokasi Interphalangeal Proximal Digiti II di Rumah Sakit USU Medan - Sihotang, Sri Nanda; Tambunan, Justinus (Poltekkes Kemenkes Kendari, 2023)
The ossa pedis is part of the lower extremity which consists of the femur, ossa pedis. The lower limbs are divided into several parts including the ossa pedis (leg bones), which consists of 26 bones and is divided into 3 parts. Dislocation is the movement of the touching surface of the bone which makes up the joint or what is usually called the joint head coming out of the cup, so that the bones that form the joint are no longer connected automatically. Radiography of the ossa pedis with suspected dislocation of the proximal digit II interphalangeal is a radiographic examination to show the anatomy and abnormalities of the ossa pedis by using x-rays. This study aims to obtain an image of the fracture of the ossa pedis from the Dorso-Plantar and Oblique projections, with optimal sharpness and detail so that it can show the bone structure and abnormalities that occur in the ossa pedis. This researcher used a qualitative type of method, using a General X-ray Unit x-ray aircraft with image processing using computed radiography (CR). Data was collected through literature studies, observations, interviews and documentation. The research results were obtained from a radiographic examination of the ossa pedis with the suspicion of proximal digit II interphalangeal dislocation with the doctor's interpretation: visible proximal digit II interphalangeal dislocation.